Prediktor Pilihan Karir Alumni Keperawatan yang Bekerja di Bidang Non-Keperawatan - Achmad Haidar Ulinuha; Ferry Efendi; Sylvia Dwi Wahyuni (FORIKES, 2022)
The nursing profession needs to maintain nursing resources to become a professional nurse. Therefore, it is necessary to know the predictors of alumni career choice in the non-nursing field. This study aims to analyze the predictors related to the career choice of nursing alumni who work in non-nursing fields. The design of this study was cross-sectional. The research subjects were 101 graduates who were selected using purposive sampling. The variables analyzed in this study were age, gender, place of residence, program, salary, cumulative achievement index (GPA) in undergraduate education and professional education. The data was obtained from the tracer study of the alumni of the Faculty of Nursing, Universitas Airlangga through filling out questionnaires, then analyzed using Chi-square and logistic regression tests. The results showed that 26.7% of nursing alumni chose to work in the non-nursing field. There is a relationship between the programs taken and the career choices of nursing alumni who work in non-nursing fields, but there is no predictor that affects the career choices of nursing alumni who work in non-nursing fields. There needs to be special attention related to nursing education programs offered through activities that can increase interest and pride in the nursing profession, so as to retain alumni working as nurses.Keywords: non-nursing; career choice; tracer study ABSTRAK Profesi keperawatan perlu mempertahankan sumber daya keperawatan untuk menjadi perawat profesional. Oleh sebab itu perlu diketahui prediktor pilihan karir alumni di bidang non-keperawatan. Penelitian ini bertujuan untuk menganalisis prediktor yang berhubungan dengan pilihan karir alumni keperawatan yang bekerja di bidang non-keperawatan. Desain penelitian ini adalah cross-sectional. Subyek penelitian adalah 101 lulusan yang dipilih menggunakan purposive sampling. Variabel yang dianalisis dalam penelitian ini adalah usia, jenis kelamin, tempat tinggal, program, gaji, indeks prestasi kumulatif (IPK) dalam pendidikan sarjana dan pendidikan profesi. Data diperoleh dari tracer study alumni Fakultas Keperawatan, Universitas Airlangga melalui pengisian kuisioner, selanjutnya dianalisis menggunakan Chi-square dan uji regresi logistik. Hasil penelitian menunjukkan bahwa 26,7% alumni keperawatan memilih bekerja di bidang non-keperawatan. Ada hubungan antara program yang diambil dengan pilihan karir alumni keperawatan yang bekerja di bidang non-keperawatan, tetapi tidak ada prediktor yang berpengaruh terhadap pilihan karir alumni keperawatan yang bekerja di bidang non-keperawatan. Perlu ada perhatian khusus terkait dengan program pendidikan keperawatan yang ditawarkan melalui kegiatan yang dapat meningkatkan rasa minat dan bangga terhadap profesi keperawatan, sehingga dapat mempertahankan alumni bekerja sebagai perawat.Kata kunci: non-keperawatan; pilihan karir; tracer study